2019
DOI: 10.1186/s12933-019-0821-5
|View full text |Cite
|
Sign up to set email alerts
|

sRAGE and early signs of cardiac target organ damage in mild hypertensives

Abstract: BackgroundSoluble Receptor for Advanced Glycation End Products (sRAGE) may be considered a marker inversely related to inflammation and its participation has been established in patients with advanced atherosclerotic vascular diseases. However, it is still unknown whether sRAGE reduction could be early metabolic change in the first stage of hypertension and initial hypertension-associated cardiac damage. We sought to determine the sRAGE values in otherwise healthy, untreated and recently diagnosed mild hyperte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
1
5
0
1
Order By: Relevance
“…Tetranectin engages in thrombolysis by binding to fibrin and converting plasminogen to plasmin, therefore lower levels of tetranectin could lead to higher rates of thrombosis [ 33 ]. Tetranectin and sRAGE have been reported to be associated with lower all-cause mortality risk and our study further highlights their potential protective effects with regard to the lungs [ 11 , 34 ].…”
Section: Discussionsupporting
confidence: 64%
“…Tetranectin engages in thrombolysis by binding to fibrin and converting plasminogen to plasmin, therefore lower levels of tetranectin could lead to higher rates of thrombosis [ 33 ]. Tetranectin and sRAGE have been reported to be associated with lower all-cause mortality risk and our study further highlights their potential protective effects with regard to the lungs [ 11 , 34 ].…”
Section: Discussionsupporting
confidence: 64%
“…More DM patients used statins, beta-blockers and angiotensin converting enzyme (ACE) inhibitors compared to subjects from the nonDM group (all p < 0.05; Table 1). The median time of DM duration was 11 [7][8][9][10][11][12][13][14][15][16][17][18] years, and DM patients had 44.2% higher glucose, 25.9% higher HbA1c, and 16.4% higher fructosamine levels compared to nonDM subjects (all p < 0.05; Table 1). DM patients were also characterized by slightly poorer renal function (Table 1).…”
Section: Resultsmentioning
confidence: 98%
“…Moreover, Hofmann et al [16] have shown in model using RAGE knock-out mice that both AGEs and RAGE are involved in the aortic leaflets calcification and subsequent AS. Low levels of both sRAGE and endogenous secretory receptor for RAGE (esRAGE), which are considered to be protective against AGEs, were shown as a very early marker of initial target organ damage in mild hypertensives [17] or a factor associated with negative coronary artery remodeling in diabetics [18]. Moreover, the concentration of sRAGE has been associated with increased arterial wall stiffening over time [19].…”
Section: Introductionmentioning
confidence: 99%
“…First, chronic inflammation was observed in individuals with higher HOMA-IR [ 14 ], which may deteriorate LV systolic function [ 26 ]. Indeed, a recent study demonstrated a significant association between soluble receptor for advanced glycation end products (sRAGE), as a marker related to inflammation, and LV remodeling [ 27 ]. Second, activation of the renin angiotensin system accompanied by elevated HOMA-IR [ 28 ] might cause reduced LVGLS [ 29 ].…”
Section: Discussionmentioning
confidence: 99%